1995
DOI: 10.1007/s002800050323
|View full text |Cite
|
Sign up to set email alerts
|

Taxol encapsulation in poly(? - caprolactone) microspheres

Abstract: Poly(epsilon-caprolactone) (PCL) microspheres containing taxol were prepared by the solvent evaporation method and tested for angiogenesis inhibition using the chick chorioallantoic membrane (CAM) model. Very high encapsulation efficiencies (95%) for taxol in PCL microspheres were obtained. In vitro release studies showed about 25% of the loaded drug was released in 6 weeks from microspheres containing 5% taxol. Studies with the CAM showed that taxol released from the microspheres induced vascular regression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…However, paclitaxel at a dose of 2 nM shortens sprouts to a striking degree and reduces cell migration in the ex vivo rat aortic ring assay (33). The antiangiogenic effect in vivo of paclitaxel as shown here and previously (9, 13, 34–38) and the fact that paclitaxel exerts a selective antiproliferative effect in human endothelial cells in vitro (32, 33, 39) makes it imperative to investigate its antiangiogenic effects, alone and in combination treatment schedules, in various preclinical models.…”
Section: Discussionmentioning
confidence: 76%
“…However, paclitaxel at a dose of 2 nM shortens sprouts to a striking degree and reduces cell migration in the ex vivo rat aortic ring assay (33). The antiangiogenic effect in vivo of paclitaxel as shown here and previously (9, 13, 34–38) and the fact that paclitaxel exerts a selective antiproliferative effect in human endothelial cells in vitro (32, 33, 39) makes it imperative to investigate its antiangiogenic effects, alone and in combination treatment schedules, in various preclinical models.…”
Section: Discussionmentioning
confidence: 76%
“…Unfortunately, this formulation has been observed to induce many adverse effects such as hypersensitivity and neurotoxicity [55]. Due to the problems of poor solubility and adverse effects associated with the available PTX formulation, scientists are trying to formulate it in many alternative and effective drug delivery systems, such as cyclodextrin [56,57], dendrimers [58], nanoparticles [59], prodrugs [60,61], liposomes [62], 2-methacryloyloxyethl phosphorylcholine polymers [63], and microspheres [64,65]. Moreover, a study performed by Mita et al involved a new drug delivery system devoid of cremophore and composed of porous PTX microspheres [66].…”
Section: Chitosan Microspheres For the Drug Delivery Of Ptxmentioning
confidence: 99%
“…5 Dordunoo and colleagues reported the first published evidence about a possible antiangiogenic activity of paclitaxel more than 15 years ago. 6 Their study showed that Taxol inhibits angiogenesis in the chick chorioallantoic membrane (CAM) model. 6 Since then, a number of studies have reported on the antiangiogenic effects of Taxol in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…6 Their study showed that Taxol inhibits angiogenesis in the chick chorioallantoic membrane (CAM) model. 6 Since then, a number of studies have reported on the antiangiogenic effects of Taxol in vitro and in vivo. 7,8 Recent studies further showed that Taxol inhibits the growth and migration of endothelial cells.…”
Section: Introductionmentioning
confidence: 99%